INFORMATION TECHNOLOGY ADOPTION IN LIBRARIES OF KERALA: A SURVEY OF SELECTED LIBRARIES IN THIRUVANANTHAPURAM - V. K. J. Jeevan Saji S. Nair (Annals of Library and Information Studies 5 1,4; 2004; 137-144, 2004)
The paper presents the results of a questionnaire based survey conducted among the premier libraries in the Thiruvananthapuram city of Kerala to assess the InformationTechnology adoption in these libraries. Results reveal that the libraries are very positive about the use of IT in libraries and many of the libraries are IT intensive.